CP-131 Review of neutropenic fever and mucositis in patients undergoing peripheral blood stem cell transplantation. (24th March 2015) - Pardo Pastor, J; March López, P; Garriga, R; Arcenillas Quevedo, P; Redondo Capafons, S; Clot Silla, E; Longoni, M; Trullàs, M; Pla, R
Abstract : Background: Peripheral blood stem cell transplantation (PBSCT) has reduced morbidity and mortality and it is probably one of the most important of the autologous transplantations. Purpose: The objective is to describe the complications (neutropenic fever and mucositis) and progress observed in haematological patients undergoing a PBSCT. Material and methods: Observational, descriptive and retrospective study carried out during 2013 in a 500-bed university hospital. All patients undergoing a PBSCT were included in the study. Two different groups were established, depending on the conditioning regime administered, depending on the usual clinical practice. Group A: Patients treated with BCNU, etoposide and cytosine arabinoside and melphalan (BEAM) Group B: Patients treated with melphalan Data collected included: sex, age, types of conditioning regimen, NF and mucositis during the bone marrow aplasia phase, as well as the patients' situation three months after the PBSCT. Results: During the bone marrow aplasia phase patients presented neutropenic fever and mucositis (Table 1 ). Three months after the PBSCT, nine patients in group A presented a complete response, two patients partial response, and one patient success. In group B, ten patients presented complete response and one patient partial response. Conclusion: Most of the patients undergoing a PBSCT presented neutropenic fever and mucositis. Eight of them required an antimicrobial treatment of high complexity and 11 required parenteral nutritional support. Three months after the PBSCT, the number of complete responses in group B was superior to those in group A. References and/or Acknowledgements: I wish to acknowledge the help provided by the pharmacy members. No conflict of interest.